Predicting the effects of integrating mineral wastes in anaerobic digestion of OFMSW using first-order and Gompertz models from biomethane potential assays. (June 2020) - Shamurad, Burhan; Gray, Neil; Petropoulos, Evangelos; Tabraiz, Shamas; Membere, Edward; Sallis, Paul
Abstract: Previous studies found mineral wastes (MW; incineration bottom ash (IBA), cement based waste (CBW), Fly ash (FA) and boiler ash (BA) are a promising resource for the macro-/micronutrients necessary for anaerobic digestion (AD) processes. The current study used first-order and modified Gompertz models from BMP assays to investigate the effects of integrating MW on the AD of OFMSW at 37 °C. Results from the first-order model showed a 45% increase in the specific growth rate of microorganisms (μ) in the MW- supplemented BMP compared to the control. Gompertz model results indicated that the IBA, CBW, FA and BA BMP amended assays obtained the highest K values (45–54 mL CH4 g VS −1 d −1 ) than the control (K ∼ 31 mL CH4 g VS −1 d −1 ), with no significant adverse effects of co-digestion of OFMSW with MW on the length of the lag phase (λ) in BMP assays (λ = 1.89 ± 0.07 days for IBA, CBW and BA amended assays compared to 1.5 ± 0.01 days for the control). However, FA amended assays had a greater λ value (3.66 ± 0.1 days). The MW provided both alkalinity and released several trace elements at concentrations within the optimal ranges for methanogenic archaea. Highlights: Mineral wastes improve methane productivity from the anaerobic digestion of MSW. Models predicted methane productivity from OFMSW amended with mineral wastes. Mineral wastes increased rates of microbial growth and methane production. Mineral wastes putatively release trace elements necessary for methanogenic archaea.